PEMANFAATAN ALPHA BRAINWAVE UNTUK MENINGKATKAN KETAHANAN EMOSIONAL ORANG TUA SELAMA MENDAMPINGI KEGIATAN BELAJAR DARI RUMAH DI DESA MEKARSARI KECAMATAN CIPARAY KABUPATEN BANDUNG - Muhammad Andriana Gaffar; Nuriska Noviantoro (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2021)
Abstract: The government has implemented policies on learning activities from home and limiting learning activities in schools as one of the efforts to suppress the spread of the COVID-19 outbreak. Over time, learning from home has an impact that is not only felt by students, but also felt directly by parents. The obstacles faced by parents of students in the Mekarsari Village area, Ciparay District, Bandung Regency are the increased cost of procuring internet data packages for the purposes of accessing online learning, the limitations of the required devices, and cognitive and psychological readiness to accompany children during learning activities at home. These various things have had an impact on the psychology of parents who serve as complete companions for children while carrying out learning from home. In connection with these problems, this service activity aims to help parents increase emotional resilience while providing assistance to children in learning activities from home. The method used is to utilize Alpha Brainwave through Parenting activities for parents in a limited environment and pay attention to health protocols. Based on the results of the implementation of Parenting activities, which consist of six phases, namely 1) Build and Maintain Rapport; 2) Calibration; 3) Map the Brain; 4) Assertiveness Installation; 5) Drop the Anchor; and 6) Provide Feedback. Through these activities, the emotional resilience of parents tends to increase while accompanying children in learning activities from home. This refers to the results of observations of the behavior and attitudes of parents carried out during service activities carried out. Thus, the use of Alpha Brainwave to increase the emotional resilience of parents in Mekarsari Village, Ciparay District, Bandung Regency has a positive impact on children while carrying out learning from home during the pandemic.Abstrak: Kebijakan aktivitas belajar dari rumah dan membatasi kegiatan pembelajaran di sekolah telah diterapkan oleh pemerintah sebagai salah satu upaya menekan tingkat penyebaran wabah COVID-19. Seiring waktu, pembelajaran dari rumah tersebut memberikan dampak yang tidak hanya dirasakan oleh peserta didik, namun juga dirasakan langsung oleh orang tua. Kendala yang dihadapi oleh orang tua peserta didik di wilayah Desa Mekarsari Kecamatan Ciparay Kabupaten Bandung ialah bertambahnya beban biaya pengadaan paket data internet untuk keperluan akses pembelajaran daring, keterbatasan gawai yang diperlukan, dan kesiapan secara kognitif maupun psikologis untuk mendampingi anak selama kegiatan pembelajaran di rumah. Berbagai hal tersebut telah berdampak pada psikologis orang tua yang bertugas sebagai pendamping anak seutuhnya selama melaksanakan pembelajaran dari rumah. Sehubungan dengan permasalahan tersebut, kegiatan pengabdian ini bertujuan untuk membantu orang tua meningkatkan ketahanan emosional selama memberikan pendampingan kepada anak dalam kegiatan belajar dari rumah. Adapun metode yang digunakan ialah dengan memanfaatkan Alpha Brainwave melalui kegiatan Parenting kepada para orang tua pada lingkungan yang terbatas dan memperhatikan protokol kesehatan. Berdasarkan hasil implementasi kegiatan Parenting yang terdiri dari enam fase, yaitu 1) Build and Maintain Rapport; 2) Calibration; 3) Map the Brain; 4) Assertiveness Installation; 5) Drop the Anchor; and 6) Provide Feedback. Melalui kegiatan tersebut, ketahanan emosional orang tua cenderung meningkat selama mendampingi anak-anak dalam kegiatan pembelajaran dari rumah. Hal tersebut mengacu pada hasil observasi perilaku dan sikap para orang tua yang dilaksanakan selama kegiatan pengabdian dilaksanakan. Dengan demikian, pemanfaatan Alpha Brainwave untuk meningkatkan ketahanan emosional orang tua di Desa Mekarsari Kecamatan Ciparay Kabupaten Bandung memberikan dampak yang positif terhadap anak selama melaksanakan pembelajaran dari rumah di masa pandemi.Keywords:Alpha Brainwave, Ketahanan Emosional, Pembelajaran dari Rumah